From Luxembourg to La Crosse and beyond 1851-1910 - Hammes, Sandra L.; Ensch, Jean 1953- ([S.L. Hammes], 2017)
"Most of the estimated 80,000 19th-century Luxembourgers emigrated from rural Luxembourg to the Midwest ... many to La Crosse, Wisconsin. ... This publication identifies and documents these immigrants, their descendants, and their lives in their new homeland."... Back cover